2005
DOI: 10.14314/polimery.2005.118
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of itaconic acid

Abstract: Polymerization of itaconic acid Summary-Poly(itaconic acid) (PIA) has been prepared by various methods namely in radical polymerization in the presence of various initiators and using water or dioxane as reaction medium, or by poly(itaconic anhydride) hydrolysis. The main purpose was to investigate the effect of method of synthesis on the chemical structure of the product. Possibilities of the structures described by Formula (II) or (III) occurring have been considered. The following methods were used for PIA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
34
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 8 publications
2
34
0
Order By: Relevance
“…IA is a key substrate for production of aliphatic, unsaturated and saturated polyesters, degradable polyamides as well as condensation polymers bearing pyrrolidine ring in the main chain . The acid is also a well‐known low reactive vinyl monomer, and its free radical polymerization typically requires long reaction times and high amounts of an initiator . Based on our previous experience with persulphate‐initiated polymerization of the acid in aqueous media and in choline‐based DESs, we have asked ourselves whether it would be possible to prepare itaconic polymers via initiator‐free radical polymerization.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…IA is a key substrate for production of aliphatic, unsaturated and saturated polyesters, degradable polyamides as well as condensation polymers bearing pyrrolidine ring in the main chain . The acid is also a well‐known low reactive vinyl monomer, and its free radical polymerization typically requires long reaction times and high amounts of an initiator . Based on our previous experience with persulphate‐initiated polymerization of the acid in aqueous media and in choline‐based DESs, we have asked ourselves whether it would be possible to prepare itaconic polymers via initiator‐free radical polymerization.…”
mentioning
confidence: 99%
“…[17][18][19] The acid is also a well-known low reactive vinyl monomer, and its free radical polymerization typically requires long reaction times and high amounts of an initiator. [20][21][22][23][24] Based on our previous experience with persulphate-initiated polymerization of the acid in aqueous media [21,24] and in choline-based DESs, [25][26][27] we have asked ourselves whether it would be possible to prepare itaconic polymers via initiator-free radical polymerization. It is well known that spontaneous thermal radical polymerization at temperature >100 °C is possible for several reactive vinyl monomers, including styrene and acrylic monomers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the polymers obtained by various methods were really PIA of the following structure: and in particular, when appropriate conditions were used, neither significant decarboxylation took place dur-ing polymerization as previously suspected [2,3] nor any formation of anhydride structures could be observed. On the other hand, based on 13 C NMR [4][5][6], one can find that PIA polymers show different tacticity depending on the synthesis process.…”
mentioning
confidence: 99%
“…An additional, very convincing argument for this structure is the founding [8] that methyl diester can be obtained by treating the product of itaconic acid polymerization with diazomethane. On the other hand, it has been found [2,3,5,6] that both conductometric and potentiometric titrations of PIA provide a result suggesting that the product contains only 50-60 % of carboxylic groups resulting from the unit structure.…”
mentioning
confidence: 99%